2015
DOI: 10.1093/ehjci/jev166
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypobaric hypoxia exposure at high altitude on left ventricular twist in healthy subjects: data from HIGHCARE study on Mount Everest

Abstract: AimsPrevious studies investigating the effect of hypoxia on left ventricle focused on its global function, an approach that may not detect a selective dysfunction of subendocardial layers that are most sensitive to an inadequate oxygen supply. In the HIGHCARE study, aimed at exploring the effects of high altitude hypoxia on multiple biological variables and their modulation by an angiotensin receptor blocker, we addressed the effects of hypobaric hypoxia on both systolic and diastolic left ventricular geometry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 34 publications
2
31
2
Order By: Relevance
“…We observed major changes in LV twist mechanics at high altitude. In accordance with recent studies (Osculati et al., ; Stembridge et al., ), we observed a greater diastolic apical rotational rate (but not basal rotational rate) and untwisting rate at high altitude compared with sea level. Moreover, the increase in untwisting rate followed the twist behaviour, because we found a correlation between these two parameters ( r = 0.64, P < 0.001).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed major changes in LV twist mechanics at high altitude. In accordance with recent studies (Osculati et al., ; Stembridge et al., ), we observed a greater diastolic apical rotational rate (but not basal rotational rate) and untwisting rate at high altitude compared with sea level. Moreover, the increase in untwisting rate followed the twist behaviour, because we found a correlation between these two parameters ( r = 0.64, P < 0.001).…”
Section: Discussionsupporting
confidence: 93%
“…Few data are available regarding the relative differences of function between the inner and outer layers of the LV wall at high altitude. Using the TSR, an indirect index of subendocardial dysfunction (Van Der Toorn et al., ), recent findings indicated that subendocardial fibres were more affected by hypoxia than subepicardial ones (Osculati et al., ). In the present study, we observed no alterations in the TSR after high‐altitude trekking, suggesting no subendocardial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Details on the cardiac ultrasound examination are described elsewhere. 21 Leftventricular diastolic pressure was evaluated by echocardiography using the Nagueh formula, 1.24 E/e'+1.91. 22 Systolic pressure-time index is considered as an estimate of myocardial needs of oxygen and represents the area under the aortic pressure curve in systole: systolic The area corresponding to isovolumic contraction time, assessed by echocardiography, was also taken into account in the evaluation of systolic pressure-time index.…”
Section: Central Bpmentioning
confidence: 99%
“…Speckle tracking echocardiography performed during the HIGH CARE STUDY on Mt. Everest demonstrates, however, an increase of the left ventricular twist (LVT) and torsion to shortening ratio in healthy trekkers at 5400 m (Osculati et al, 2015). Both parameters allow assessing predominantly the function of the subendocardial myocardium, which is most sensitive to inadequate oxygen supply.…”
Section: Speckle Tracking Echocardiography Suggests ''Subclinical'' Ementioning
confidence: 99%